EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK BERBANTU MEDIA WORDWALL TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Naylatus Sa’adah; Nurul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the limited research on the effectiveness of the talking stick learning model assisted by wordwall media in improving student learning outcomes, particularly in Pancasila Education. The aim of this research is to measure the influence of the model on the learning outcomes of fourth-grade students at SDN Kedensari 1. The study used a quantitative method with a One Group Pretest-Posttest Design. The sample consisted of 22 students selected through total sampling. The instrument used a test that had been validated and tested for reliability. The analysis results showed a significant improvement, with the average pretest score increasing from 66.1 to 83.1 in the posttest. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect. The study concludes that the talking stick model assisted by wordwall is effective in improving Pancasila Education learning outcomes. The findings suggest that this model should be integrated into learning to enhance student engagement.